The Dead Are Dead/Ancestors Never Die: Migrants, Rural Linkages, and Religious Change in Northeastern Madagascar - Tilghman, Laura M. (Journal of religion in Africa, 2018)
This manuscript explores the dynamic between religion and rural-urban linkages in northeastern Madagascar. I find that church leaders have coalesced around two competing narratives of ancestors. Catholic churches see some types of migrant linkages (e.g., burial in the rural family tomb and participation in rural ancestral rituals) as being in line with Christian beliefs, while Protestant churches see these same activities as morally questionable or potentially satanic. To some degree Protestant migrants exert agency in the face of these religious teachings, and do not view their religion as an impediment to maintaining rural connections. However, quantitative analysis of rural-urban linkage behavior over a twelve-month period shows that Protestants have weaker rural ties compared to Catholics, even for behaviors that are not the focus of religious prohibitions. I offer several explanations for this finding. Protestant migrants are less motivated to invest in all types of rural linkages due to family conflicts after conversion, uncertainty about burial in the rural family tomb, reduced opportunities to develop affective ties with kin, and economic motivations to reduce rural demands on their urban wages.